2016
DOI: 10.1007/s11010-016-2878-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases: mechanisms and downstream targets in inflammation-mediated obesity and insulin resistance

Abstract: Obesity induced low-grade inflammation (metaflammation) impairs insulin receptor signaling (IRS). This has been implicated in the development of insulin resistance. Insulin signaling in the target tissues is mediated by stress kinases such as p38 mitogen-activated protein kinase (MAPK), c-Jun NH2-terminal kinase (JNK), inhibitor of NF-kB kinase complex beta (IKKβ), AMP activated protein kinase (AMPK), protein kinase C (PKC), Rho associated coiled-coil containing protein kinase (ROCK) and RNA-activated protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 175 publications
1
87
0
1
Order By: Relevance
“…Besides, G6Pase , FBPase and PEPCK genes are responsible for gluconeogenesis. It has been well established that the downregulation of G6Pase , FBPase and PEPCK genes can significantly inhibit gluconeogenesis, and subsequent reduce blood glucose levels . In the present study, BMH473 inhibited hepatic steatosis and reduced hepatic lipid contents in obese T2DM rats, by regulating the protein expressions of PPAR‐α and SREBP‐1 c, as well as the mRNA expressions of LDLR , FAS and Scd 1 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Besides, G6Pase , FBPase and PEPCK genes are responsible for gluconeogenesis. It has been well established that the downregulation of G6Pase , FBPase and PEPCK genes can significantly inhibit gluconeogenesis, and subsequent reduce blood glucose levels . In the present study, BMH473 inhibited hepatic steatosis and reduced hepatic lipid contents in obese T2DM rats, by regulating the protein expressions of PPAR‐α and SREBP‐1 c, as well as the mRNA expressions of LDLR , FAS and Scd 1 .…”
Section: Discussionsupporting
confidence: 51%
“…Inflammation in WAT is one of the common pathological changes in obese T2DM rats. Inflammatory pathways have been increasingly recognized as novel factors contributed to the development of T2DM, especially insulin resistance . Several studies have demonstrated the elevated levels of pro‐inflammatory cytokines (TNF‐α, IL‐1 β and IL‐6) in obesity and T2DM .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia and insulin resistance cause cells to lose insulin sensitivity and inhibit their ability to uptake glucose. The IR, with the signal increasing through a cascade of molecules (PI3K/Akt signaling pathway), is deteriorated by hyperglycemia and insulin resistance, which worsens the ability of GLUT to facilitate glucose uptake into the cells (Babu, Liu, & Gilbert, ; Nandipati et al, ; Oliveira et al, ) In this study, the HFD reduced the protein expressions of AMPK, IR, IRS‐1, IRS‐2, PI3K, Akt/PKB, GLUT‐1, and GLUT‐4 (Figure ). Although the insulin level increased, the proteins related to glucose uptake were impaired and the fasting blood glucose, HbA1c, and OGTT levels were higher in the HFD group compared to the RD group (Table ).…”
Section: Discussionmentioning
confidence: 59%
“…p38 MAPKs are stress-responsive MAPKs that are activated by a variety of stresses in addition to cytokines and growth factors [10, 32, 33]. The p38 MAPK signaling module consists of MAPKKK-MKK3/4/6-p38MAPK [10].…”
Section: P38 Mapk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 99%